6.150 Problems 14901 to 15000

Table 6.299: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

14901

\[ {}y^{\prime \prime }+4 y^{\prime }+13 y = -3 \,{\mathrm e}^{-2 t} \]

14902

\[ {}y^{\prime \prime }+7 y^{\prime }+10 y = {\mathrm e}^{-2 t} \]

14903

\[ {}y^{\prime \prime }-5 y^{\prime }+4 y = {\mathrm e}^{4 t} \]

14904

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 4 \,{\mathrm e}^{-3 t} \]

14905

\[ {}y^{\prime \prime }+6 y^{\prime }+8 y = {\mathrm e}^{-t} \]

14906

\[ {}y^{\prime \prime }+7 y^{\prime }+12 y = 3 \,{\mathrm e}^{-t} \]

14907

\[ {}y^{\prime \prime }+4 y^{\prime }+13 y = -3 \,{\mathrm e}^{-2 t} \]

14908

\[ {}y^{\prime \prime }+7 y^{\prime }+10 y = {\mathrm e}^{-2 t} \]

14909

\[ {}y^{\prime \prime }+4 y^{\prime }+3 y = {\mathrm e}^{-\frac {t}{2}} \]

14910

\[ {}y^{\prime \prime }+4 y^{\prime }+3 y = {\mathrm e}^{-2 t} \]

14911

\[ {}y^{\prime \prime }+4 y^{\prime }+3 y = {\mathrm e}^{-4 t} \]

14912

\[ {}y^{\prime \prime }+4 y^{\prime }+20 y = {\mathrm e}^{-\frac {t}{2}} \]

14913

\[ {}y^{\prime \prime }+4 y^{\prime }+20 y = {\mathrm e}^{-2 t} \]

14914

\[ {}y^{\prime \prime }+4 y^{\prime }+20 y = {\mathrm e}^{-4 t} \]

14915

\[ {}y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-t} \]

14916

\[ {}y^{\prime \prime }-5 y^{\prime }+4 y = 5 \]

14917

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 2 \]

14918

\[ {}y^{\prime \prime }+2 y^{\prime }+10 y = 10 \]

14919

\[ {}y^{\prime \prime }+4 y^{\prime }+6 y = -8 \]

14920

\[ {}y^{\prime \prime }+9 y = {\mathrm e}^{-t} \]

14921

\[ {}y^{\prime \prime }+4 y = 2 \,{\mathrm e}^{-2 t} \]

14922

\[ {}y^{\prime \prime }+2 y = -3 \]

14923

\[ {}y^{\prime \prime }+4 y = {\mathrm e}^{t} \]

14924

\[ {}y^{\prime \prime }+9 y = 6 \]

14925

\[ {}y^{\prime \prime }+2 y = -{\mathrm e}^{t} \]

14926

\[ {}y^{\prime \prime }+4 y = -3 t^{2}+2 t +3 \]

14927

\[ {}y^{\prime \prime }+2 y^{\prime } = 3 t +2 \]

14928

\[ {}y^{\prime \prime }+4 y^{\prime } = 3 t +2 \]

14929

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = t^{2} \]

14930

\[ {}y^{\prime \prime }+4 y = t -\frac {1}{20} t^{2} \]

14931

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 4+{\mathrm e}^{-t} \]

14932

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{-t}-4 \]

14933

\[ {}y^{\prime \prime }+6 y^{\prime }+8 y = 2 t +{\mathrm e}^{-t} \]

14934

\[ {}y^{\prime \prime }+6 y^{\prime }+8 y = 2 t +{\mathrm e}^{t} \]

14935

\[ {}y^{\prime \prime }+4 y = t +{\mathrm e}^{-t} \]

14936

\[ {}y^{\prime \prime }+4 y = 6+t^{2}+{\mathrm e}^{t} \]

14937

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \cos \left (t \right ) \]

14938

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 5 \cos \left (t \right ) \]

14939

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \sin \left (t \right ) \]

14940

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 2 \sin \left (t \right ) \]

14941

\[ {}y^{\prime \prime }+6 y^{\prime }+8 y = \cos \left (t \right ) \]

14942

\[ {}y^{\prime \prime }+6 y^{\prime }+8 y = -4 \cos \left (3 t \right ) \]

14943

\[ {}y^{\prime \prime }+4 y^{\prime }+13 y = 3 \cos \left (2 t \right ) \]

14944

\[ {}y^{\prime \prime }+4 y^{\prime }+20 y = -\cos \left (5 t \right ) \]

14945

\[ {}y^{\prime \prime }+4 y^{\prime }+20 y = -3 \sin \left (2 t \right ) \]

14946

\[ {}y^{\prime \prime }+2 y^{\prime }+y = \cos \left (3 t \right ) \]

14947

\[ {}y^{\prime \prime }+6 y^{\prime }+8 y = \cos \left (t \right ) \]

14948

\[ {}y^{\prime \prime }+6 y^{\prime }+8 y = 2 \cos \left (3 t \right ) \]

14949

\[ {}y^{\prime \prime }+6 y^{\prime }+20 y = -3 \sin \left (2 t \right ) \]

14950

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 2 \cos \left (2 t \right ) \]

14951

\[ {}y^{\prime \prime }+3 y^{\prime }+y = \cos \left (3 t \right ) \]

14952

\[ {}y^{\prime \prime }+4 y^{\prime }+20 y = 3+2 \cos \left (2 t \right ) \]

14953

\[ {}y^{\prime \prime }+4 y^{\prime }+20 y = {\mathrm e}^{-t} \cos \left (t \right ) \]

14954

\[ {}y^{\prime \prime }+9 y = \cos \left (t \right ) \]

14955

\[ {}y^{\prime \prime }+9 y = 5 \sin \left (2 t \right ) \]

14956

\[ {}y^{\prime \prime }+4 y = -\cos \left (\frac {t}{2}\right ) \]

14957

\[ {}y^{\prime \prime }+4 y = 3 \cos \left (2 t \right ) \]

14958

\[ {}y^{\prime \prime }+9 y = 2 \cos \left (3 t \right ) \]

14959

\[ {}y^{\prime \prime }+4 y = 8 \]

14960

\[ {}y^{\prime \prime }-4 y = {\mathrm e}^{2 t} \]

14961

\[ {}y^{\prime \prime }-4 y^{\prime }+5 y = 2 \,{\mathrm e}^{t} \]

14962

\[ {}y^{\prime \prime }+6 y^{\prime }+13 y = 13 \operatorname {Heaviside}\left (t -4\right ) \]

14963

\[ {}y^{\prime \prime }+4 y = \cos \left (2 t \right ) \]

14964

\[ {}y^{\prime \prime }+3 y = \operatorname {Heaviside}\left (t -4\right ) \cos \left (5 t -20\right ) \]

14965

\[ {}y^{\prime \prime }+4 y^{\prime }+9 y = 20 \operatorname {Heaviside}\left (t -2\right ) \sin \left (t -2\right ) \]

14966

\[ {}y^{\prime \prime }+3 y = \left \{\begin {array}{cc} t & 0\le t <1 \\ 1 & 1\le t \end {array}\right . \]

14967

\[ {}y^{\prime \prime }+3 y = 5 \delta \left (t -2\right ) \]

14968

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = \delta \left (t -3\right ) \]

14969

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = -2 \delta \left (t -2\right ) \]

14970

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = \delta \left (t -1\right )-3 \delta \left (t -4\right ) \]

14971

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = {\mathrm e}^{-2 t} \sin \left (4 t \right ) \]

14972

\[ {}y^{\prime \prime }+y^{\prime }+5 y = \operatorname {Heaviside}\left (t -2\right ) \sin \left (4 t -8\right ) \]

14973

\[ {}y^{\prime \prime }+y^{\prime }+8 y = \left (1-\operatorname {Heaviside}\left (t -4\right )\right ) \cos \left (t -4\right ) \]

14974

\[ {}y^{\prime \prime }+y^{\prime }+3 y = \left (1-\operatorname {Heaviside}\left (t -2\right )\right ) {\mathrm e}^{-\frac {t}{10}+\frac {1}{5}} \sin \left (t -2\right ) \]

14975

\[ {}y^{\prime \prime }+16 y = 0 \]

14976

\[ {}y^{\prime \prime }+4 y = \sin \left (2 t \right ) \]

14977

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 0 \]

14978

\[ {}y^{\prime \prime }+16 y = t \]

14979

\[ {}y^{\prime } = 3-\sin \left (x \right ) \]

14980

\[ {}y^{\prime } = 3-\sin \left (y\right ) \]

14981

\[ {}y^{\prime }+4 y = {\mathrm e}^{2 x} \]

14982

\[ {}x y^{\prime } = \arcsin \left (x^{2}\right ) \]

14983

\[ {}y y^{\prime } = 2 x \]

14984

\[ {}y^{\prime \prime } = \frac {1+x}{x -1} \]

14985

\[ {}x^{2} y^{\prime \prime } = 1 \]

14986

\[ {}y^{2} y^{\prime \prime } = 8 x^{2} \]

14987

\[ {}y^{\prime \prime }+3 y^{\prime }+8 y = {\mathrm e}^{-x^{2}} \]

14988

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime } = 0 \]

14989

\[ {}y^{\prime } = 4 x^{3} \]

14990

\[ {}y^{\prime } = 20 \,{\mathrm e}^{-4 x} \]

14991

\[ {}x y^{\prime }+\sqrt {x} = 2 \]

14992

\[ {}\sqrt {x +4}\, y^{\prime } = 1 \]

14993

\[ {}y^{\prime } = x \cos \left (x^{2}\right ) \]

14994

\[ {}y^{\prime } = x \cos \left (x \right ) \]

14995

\[ {}x = \left (x^{2}-9\right ) y^{\prime } \]

14996

\[ {}1 = \left (x^{2}-9\right ) y^{\prime } \]

14997

\[ {}1 = x^{2}-9 y^{\prime } \]

14998

\[ {}y^{\prime \prime } = \sin \left (2 x \right ) \]

14999

\[ {}y^{\prime \prime }-3 = x \]

15000

\[ {}y^{\prime \prime \prime \prime } = 1 \]